New indicators of health among adolescent drug users and evaluation of drug policies comparing countries - Elena Ventura; Harrison Wagner; Carla Rossi (Epidemiology, Biostatistics and Public Health)
By correlating essential features of the national drug legislations and policies of some European countries and various indicators of consumption and health of consumers, interesting patterns emerge. We conclude that it is the correct balance between a drug policy aimed at prevention, rehabilitation, and a less restrictive legislation, that, on the basis of what we have analyzed and measured, has a positive effect on drug consumption and that indicators are efficient and should be applied regularly to compare quantitatively country policies to identify best practices.